Response of two broccoli cultivars to foliar application of Lithovit fertilizer under two planting methods - Nassef, Dalia M. T.; Nabeel, A. H. M. (2012)
A field experiment was conducted in Agriculture Farm, El-Azhar University, Assiut Branch in 2010-2011 and 2011-2012 seasons to study the effect of foliar Lithovit fertilization at different doses on yield and growth of two broccoli cultivars using two planting methods. Randomized Complete Blocks Design (RCBD) in split-spilt-plot arrangements with three repli- cates was used. The two planting methods (direct sowing and transplants) occupied the main plots. While, the Broccoli cultivars (Calabrese and Waltham 29) were arranged in the sub- plots. The Lithovit levels were; 0% (control), 0.05%, 0.10 % and 0.20 %.These concentrations were distributed in the sub- subplots. The obtained results revealed that planting method affected significantly most of the studied traits. But insignificant differences were detected for number of branches/plant in both seasons and No. of curds/plant, main head weight and total head yield (ton/feddan) in the first season. Most of studied traits reacted significantly to transplanting method except plant height.
Includes reference.
Summary in Arabic.
1
Keywords: Broccoli -- Varieties; Broccoli -- Yields; Broccoli -- Growth; Foliar feeding